Optimizing Lerak product marketing content through feed content design strategies and motion graphics on social media platforms: a design thinking approach - El Chidtian, Aileena Solicitor Costa Rica; Nisa , Atika Khalifatu; Aji , Restu Ismoyo (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
The increasing competition in eco-friendly product marketing has driven the need for innovative digital promotion strategies, particularly on social media platforms. Lerak, a traditional natural detergent, requires an effective communication approach to enhance public awareness and market reach. This study aims to optimize social media marketing content for Demibumi’s lerak products by focusing on feed and motion graphics design strategies across Instagram, Facebook, and YouTube. Employing a qualitative method with a design thinking approach, the research followed five key stages: problem identification, audience analysis, idea generation, prototyping, and evaluation. Data were gathered through observation, content analysis, and feedback from target audiences. The results indicate that combining educational visual elements with storytelling in both static feed designs and short-form video content (reels) significantly improves visual appeal, audience engagement, and promotional efficiency. Educational infographics increased user retention, while narrative-driven videos fostered emotional connection and brand trust. The study concludes that a well-structured design strategy integrating informative content and compelling narratives can enhance the effectiveness of social media campaigns for eco-friendly products. The strategic contribution of this research lies in offering a replicable creative content model that integrates design aesthetics, brand storytelling, and audience relevance, serving as a reference for sustainable product marketing in digital environments.